PENGARUH DEFISIT ANGGARAN TERHADAP DEFISIT TRANSAKSI BERJALAN DI INDONESIA - Nizar, Muhammad Afdi (Badan kebijakan Fiskal, 2013)
This study aims to determine the effect of budget deficits on the current accounts deficit in Indonesia during 1990 - 2012. Based on quarterly time series data and using VAR model, the results of this study indicate that: (i) a positive effect of the budget deficit on the current account deficit. In the period 1990 - 2012 the effect of budget deficits is relatively small and rapid (one quarter), while in the period 1990-1997 budget deficits had greater influence with a longer duration (a semester) on current accounts deficit, and (ii) the results of this study confirm and in line with the twin deficit hypothesis. Therefore, the government should take concrete steps to reduce imports of oil (fuel). Because of fuel imports potentially add to the current accounts deficit and also the amount of fuel subsidies (and deficit) in the state budget